Muscle pre-activation strategies play a role in modulating Kvert for change of direction manoeuvres: An observational study - Serpell, B. G.; Ball, N. B.; Scarvell, J. M.; Buttfield, A.; Smith, P. N. (Journal of Electromyography and Kinesiology, 2014)
The aim of the study presented in this paper was to establish if a relationship existed between lower limb muscle pre-activation strategies and vertical stiffness (Kvert). Participants from a professional rugby union club all performed a multidirectional hopping task on a force platform which measured Kvert. Muscle activity was concurrently measured for the gluteus maximus, vastus lateralis, vastus medialis, biceps femoris, semimembranosus, and medial gastrocnemius using electromyography and the activity of those muscles in the 100 ms prior to foot contact (pre-activation) was analysed. Moderate to strong positive relationships were typically seen for Kvert and muscle pre-activation for each muscle when normalized to maximum voluntary contraction. Pre-activation cocontraction of the muscles surrounding the knee joint also showed a typically moderate relationship with Kvert and peak muscle activation of antagonist muscles at the knee joint were typically similar. Results suggest that muscle pre-activation strategies play a role in modulating Kvert for change of direction manoeuvre.